Effect of crystallizer design and operational parameters on the batch crystallization of ibuprofen I: experimental. Issue 1 (1st January 2022) - Pakhare, Achyut; Mathpati, Channamallikarjun; Dalvi, Vishwanath H.; Joshi, Jyeshtharaj; Patil, Raosaheb; Kalekudithi, Ekambara
ABSTRACT: Ibuprofen is widely used as an anti-inflammatory drug. Ibuprofen crystallized from non-polar hexane exhibits needle morphology, while from polar solvents, it exhibits a plate or polyhedral morphology. Among these, needle morphology possesses poor flow properties and poses difficulty in downstream processing. The flow properties (indicated by the bulk density) can be improved by manipulating heating–cooling cycles, hydrodynamics in the crystallizer, and seeding. In the present work, experiments were carried out to investigate the effect of various design and operating parameters such as impeller design, impeller speed, seed size, % seed quantity, and cooling profiles on ibuprofen crystal characteristics using hexane as a solvent. Closed clear impellers, such as helical ribbon impeller exhibits higher bulk density and average crystal size compared to open type impellers. Beyond certain agitation speeds, the average crystal size is affected by the breakage mechanism. The seed size and seed quantity showed a minor impact on bulk density and average crystal size.